Personal and Corporate Saving in South Africa. - Aron, J; Muellbauer, J (CEPR, 2000)
Low domestic saving rates in South Africa may perpetuate a low-growth trap. The decline in government saving, a major reason for the overall decline in saving, is now being reversed. However, personal saving rates have fallen since 1993, and corporate rates since 1995, and both may decline further with lower real interest rates. It is important to understand both personal and corporate saving behaviour in order to formulate policies to raise the domestic saving rate in line with the needs of economic growth. This article summarizes our previous work on the household sector, emphasizing the role of financial liberalization, assets, and income expectations, and it explains sectoral links and policy implications. Further, it analyses South Africa's corporate saving rate in detail. Models are developed both for the share of profits in national income, including the roles of the terms of trade, tax effects, and the price to unit labour cost margin, and for the share of corporate saving in profits, which is found to depend on inflation, the real interest rate, dividend taxation, and financial liberalization. Corporate saving is remarkably underresearched, given its importance in many economies. This research thus puts the saving and growth concerns of Kaldor into a modern empirical context.